Multiwavelength Digital Holographic Imaging and Phase Unwrapping of Protozoa Using Custom Fiji Plug-ins - Cohoe, David; Hanczarek, Iulia; Wallace, J. Kent; Nadeau, Jay (Frontiers in Physics, 2019)
Multiwavelength digital holographic microscopy (DHM) has been used to improve phase reconstructions of digital holograms by reducing 2π phase ambiguities. However, most samples used as test images have been solid or adhered to a surface, making it easy to determine focal planes and correct for chromatic aberration. In this study we apply 3-wavelength off-axis DHM to swimming protozoa containing distinct spectral features such as chlorophyll and carotenoids. We reconstruct the holograms into amplitude and phase images using the angular spectrum method. Methods for noise subtraction, chromatic aberration correction, and image registration are presented for both amplitude and phase. Approaches to phase unwrapping are evaluated and compared to expected results from simulated holograms. The algorithms used are implemented in plug-ins using the open source Fiji platform and are available for use, significantly expanding the open-source software available for DHM.